Role of large‐ and fine‐scale variables in predicting catch rates of larval Pacific lamprey in the Willamette Basin, Oregon. Issue 2 (19th December 2014) - Schultz, Luke D.; Mayfield, Mariah P.; Sheoships, Gabe T.; Wyss, Lance A.; Clemens, Benjamin J.; Whitlock, Steven L.; Schreck, Carl B.
Abstract: Pacific lamprey Entosphenus tridentatus is an anadromous fish native to the Pacific Northwest of the USA. That has declined substantially over the last 40 years. Effective conservation of this species will require an understanding of the habitat requirements for each life history stage. Because its life cycle contains extended freshwater rearing (3–8 years), the larval stage may be a critical factor limiting abundance of Pacific lamprey. The objective of our study was to estimate the influence of barriers and habitat characteristics on the catch‐per‐unit‐effort (CPUE) of larval Pacific lamprey in the Willamette River Basin, Oregon, USA. We sampled lampreys at multiple locations in wadeable streams throughout the basin in 2011–13 and used an information theoretic approach to examine the relative influence of fine‐ and large‐scale predictors of CPUE. Pacific lamprey was observed across the basin, but its relative abundance appeared to be limited by the presence of natural and artificial barriers in some sub‐basins. Lower velocity habitats such as off‐channel areas and pools contained higher densities of larval lamprey; mean Pacific lamprey CPUE in off‐channel habitats was 4 and 32 times greater than in pools and riffles respectively. Restoration and conservation strategies that improve fish passage, enhance natural hydrologic and depositional processes and increase habitat heterogeneity will likely benefit larval Pacific lamprey.